Surface-modified high-entropy lithium-manganese-rich positive electrode material as well as preparation method and application thereof

By co-doping high-d-state orbital elements and low-electronegative elements in lithium-rich manganese positive electrode materials and building a high-entropy structure on the surface, the problem of structural degradation of the material during the cycle is solved, the cycle performance and structural stability are significantly improved, and voltage attenuation is reduced.

CN119764379APending Publication Date: 2025-04-04ZHENGZHOU ZHONGKE EMERGING IND TECH RES INST +2

Patent Information

Application Number
CN202411886679.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing lithium-rich manganese positive electrode materials have severe structural degradation during the cycle, resulting in poor cycle stability, voltage attenuation and low-rate performance, limiting their commercial applications.

Method used

By co-doping a small amount of high-d-state orbital elements and low-electronegative elements in lithium-rich manganese positive electrode materials, the electrostatic field is adjusted, the |O2p band is expanded, the (TM-O)* band overlap is enhanced, the energy band gap is reduced, the anion redox reversibility is improved, and the energy band structure is changed through the high entropy surface, the diversity and distortion energy of Mn4+ local structure are increased, and the structural stability is improved.

Benefits of technology

Without affecting capacity, the cycling performance of the material is significantly improved, voltage attenuation is reduced, structural stability is enhanced, and the precise design and controllable preparation of the rich layered oxide cathode material is realized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764379A_ABST
    Figure CN119764379A_ABST
Patent Text Reader

Abstract

The invention discloses a surface-modified high-entropy lithium-rich manganese positive electrode material as well as a preparation method and application thereof, and the surface-modified high-entropy lithium-rich manganese positive electrode material is represented by a general formula Li1 + xNi0. 13Co0. 13Mn0. 54MyNzO2-wAw. The specific preparation method comprises the following steps: respectively weighing a nickel-cobalt-manganese compound, a lithium salt, an additive I and an additive II, uniformly mixing, carrying out high-temperature calcination in a muffle furnace, cooling, crushing, crushing, and screening to obtain the surface-modified high-entropy lithium-rich manganese positive electrode material. And mixing with an additive III, and carrying out secondary sintering to prepare the surface high-entropy lithium-rich manganese positive electrode material. According to the method, different electrostatic fields are generated through co-doping of a high-d-state orbital element and a low-electronegativity element, an O2p band is expanded, overlapping between the O2p band and a (TM-O) * band is enhanced, an energy band gap is reduced, and anion oxidation reduction reversibility is promoted; by constructing a surface high-entropy change energy band structure, the diversity and distortion energy of a Mn < 4 + > local structure are increased, and the formation energy of oxygen vacancies and the migration energy of transition metal ions are improved. Through accurate design and controllable preparation of the lithium-rich manganese material and multi-strategy coordinated regulation and control of an energy band structure, the cycle performance and the voltage attenuation phenomenon of the lithium-rich manganese-based positive electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode material for lithium ion batteries, and in particular to a surface modified high entropy lithium-rich manganese positive electrode material and a preparation method and application thereof. Background Art

[0002] As new energy vehicles have higher and higher requirements for driving range, the energy density, cycle performance and safety performance of lithium-ion batteries are also facing higher challenges. 1+w Ni x Co y Mn z O2) with high specific capacity (~250mAh g -1 ), high operating voltage (~3.6 V) and low cost, and is expected to become the positive electrode material for the next generation of commercial high-energy-density lithium batteries.

[0003] The high capacity of Li-rich manganese materials originates from the co-participation of oxygen anions and transition metal (TM) cations in charge compensation. However, structural degradation during cycling associated with irreversible oxygen redox poses great challenges, including poor cycling stability, voltage decay, and low rate performance, hindering their commercial application. The reversibility of oxygen-redox is limited by the non-bonded O 2p The influence of the degree of overlap of the orbital with the TM-O bonding orbital depends on the octahedral configuration formed by the local ligand. In general, the activity and reversibility of oxygen-redox are determined by the "Li-O-Li" configuration and the "OLi2TM4" octahedron. Therefore, adjusting the configuration and ligands can fundamentally solve the problem of O2 release and the problem of continuous structural weakening of the lithium-rich cathode from the surface to the inside, thereby developing lithium-rich materials with longer life.

[0004] Application number 202410649999.6: Dissolve the lithium source, nickel source, manganese source and compound containing A to obtain solution 1, then add citric acid to obtain solution 2, add solution 2 to solution 1, adjust the pH to form a gel, and obtain a lithium-rich cobalt-free high-entropy positive electrode material after drying, grinding and calcining. Application number 202311821605.2: Mix the ammonia solution of nickel salt, manganese salt and sodium carbonate, adjust the pH to obtain a precipitate, add the salt solution of doped ions, sinter and ball-mill the powder, then add lithium carbonate and ion-doped oxides for ball milling and sintering, and then add a carbon source to obtain a high-entropy doped lithium-rich manganese material. Application number 202410885807.1: Prepare an aluminum-niobium co-doped nickel-manganese precursor by coprecipitation, then pass the doping coating solution into the nickel-manganese precursor, and then sinter to obtain a high-entropy lithium-rich manganese-based precursor. Application number 202310472877.X pre-sinters the mixture of lithium source, manganese source, nickel source, cobalt source and additives, grinds the pre-sintered material with zirconium oxide balls of different particle sizes in a sand mill, and then presses it with a tablet press, and then sinters it at high temperature to obtain a high-entropy lithium-rich material for marine environment. Application number 202410368800.2 calcines the lithium-rich manganese precursor with the lithium source, and then hydrothermally reacts it with a metal fluoride solution A, and anneals to obtain a high-entropy lithium-rich manganese-based core-shell material without defective core-shell. Application number 202211421676.9 dissolves the lithium source, nickel source and manganese source with several soluble salts of the M element, adds citric acid, causes the citric acid to hydrolyze and condense with the metal ions, and sinters the gel to obtain a medium-entropy / high-entropy lithium-rich cathode material. Application No. 202410502077.2: Polyacrylonitrile and polymethyl methacrylate are dissolved in dimethylformamide, lithium salt, manganese salt, nickel salt, cobalt salt, aluminum salt and TM salt are dissolved in dimethylformamide, the mixed metal salt solution is added to the polymer solution, and the precursor nanofibers are prepared by high-voltage electrospinning, and then calcined to obtain high-entropy lithium-rich manganese-based porous oxide nanofibers. Application No. 202410233753.0: A mixed solution of manganese source, nickel source, cobalt source and TM is used to obtain a high-entropy lithium-rich manganese precursor by coprecipitation, and then ground and calcined with a lithium source to obtain a voltage-free high-entropy lithium-rich manganese material. Application No. 202211113380.0: A mixed solution of Mn and A is prepared, a precursor is prepared by coprecipitation, and the precursor is mixed with a lithium source and sintered to obtain a lithium-rich manganese-based high-entropy positive electrode material. Application No. 202311072480.X: The lithium source, M1 metal salt, M2 metal salt, and anion-containing substance A are dissolved in an alcohol solution to obtain liquid A, and the soluble substance under acidic conditions and the complexing agent are co-dissolved in an alcohol solution to obtain liquid B, and liquid B is added dropwise to liquid A and evaporated at a constant temperature to obtain a gel, which is then pressed into sheets, calcined at high temperature, quenched in liquid nitrogen, and ball milled to obtain a single crystal high-entropy lithium-rich positive electrode material.Application No. 202410096414.2 prepares a metal salt solution containing a manganese source, a nickel source, a cobalt source, a copper source, a zinc source, and a magnesium source, adds the metal salt solution and a precipitant to the bottom liquid for precipitation to obtain a precursor, and mixes the precursor with a lithium source and calcines to obtain a lithium-rich manganese-based positive electrode material. Previous patents on lithium-rich materials mainly focus on improving capacity attenuation and improving cycle performance, but there is little research on energy band regulation. The patent of this invention expands the |O2p band by co-doping high d-state orbital elements and low electronegativity elements, enhances the overlap between the |O2p band and the (TM-O)* band, narrows the band gap, and promotes the reversibility of anion redox; the surface high entropy changes the band structure and increases Mn. 4+ The diversity and distortion energy of local structures increase the formation energy of oxygen vacancies and the migration energy of transition metal ions. Multiple strategies are used to coordinately regulate the band structure, achieving the precise design and controllable preparation of the rich layered oxide cathode materials, thereby improving the cycle performance and reducing voltage decay. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a surface modified high entropy lithium-rich manganese positive electrode material and its preparation method and application. Under the premise of not affecting the capacity, a small amount of high d-state orbital elements and low electronegativity elements are co-doped to generate different electrostatic fields, expand the |O2p band, enhance the overlap between the |O2p band and the (TM-O)* band, narrow the band gap, and promote the anion redox reversibility; the surface high entropy changes the band structure, increases the Mn 4+ The diversity and distortion energy of the local structure increase the formation energy of oxygen vacancies and the migration energy of transition metal ions, enhance the structural stability and inhibit the lattice distortion, thus increasing the Mn 4+ The local structural adaptability of the material enhances the structural stability. By doping heterostructures and constructing surface high entropy, multiple strategies are used to coordinately regulate the band structure, achieving precise regulation of the material structure, thereby improving the cycle performance and reducing voltage decay.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: A surface modified high entropy lithium-rich manganese cathode material, with the general formula Li 1+x Ni 0.13 Co 0.13 Mn 0.54 M y N z O 2-w A wIt means that M is selected from one of the elements with high d-state orbital Cr, Mo, W, V, Nb, and Ta, A is selected from one of the elements with high electronegativity F, S, Se, and Cl, N is selected from at least four elements of Mg, Nb, Cr, Ti, Mo, Al, B, Ca, Zn, Sn, W, Ce, Zr, and Sr, 0.18≤x≤0.25, 0<y≤0.01, 0<z≤0.02, and 0<w≤0.01; The present invention also provides a preparation method of the surface modified high-entropy lithium-rich manganese positive electrode material, which comprises the following steps: respectively weighing a nickel-cobalt-manganese compound, a lithium source, an additive I, and an additive II, mixing them evenly, calcining them at a high temperature in a muffle furnace, crushing, pulverizing, and screening them after cooling, and then mixing them with the additive III and performing secondary sintering to obtain the high-entropy lithium-rich manganese positive electrode material.

[0007] Furthermore, the nickel-cobalt-manganese compound is nickel-cobalt-manganese hydroxide, nickel-cobalt-manganese carbonate, or nickel-cobalt-manganese oxide, with an average particle size D50 of 1-15 μm, wherein the nickel-cobalt-manganese oxide is obtained by pre-calcining the nickel-cobalt-manganese hydroxide or nickel-cobalt-manganese carbonate at a high temperature of 300-700° C. for 1-10 hours.

[0008] Furthermore, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide monohydrate, lithium bicarbonate, lithium oxalate, lithium nitrate or lithium acetate, the molar ratio of the lithium source to the nickel-cobalt-manganese compound is (1.30-1.35):1, the lithium sources used are all battery grade, and the average particle size D50 is 3-15 μm.

[0009] Furthermore, the additive I is a compound containing anions F, S, Se, and Cl, the additive II is a compound containing high d-state orbitals Cr, Mo, W, V, Nb, and Ta, the average particle size D50 of the additive I and the additive II is 10-100 nm; the molar ratio of the additive I to the nickel-cobalt-manganese compound is a, 0<a≤0.01, and the molar ratio of the additive II to the nickel-cobalt-manganese compound is b, 0<b≤0.01. The dosage of the additive I and the additive II needs to be strictly limited, and excessive doping has a negative impact on the electrochemical properties of the material.

[0010] Furthermore, the additive III is a mixture of at least four kinds of oxides and hydroxides of Mg, Nb, Cr, Ti, Mo, Al, B, Ca, Zn, Sn, W, Ce, Zr, and Sr, and the average particle size D50 of the additive III is 10-100 nm; the molar ratio of the additive III to the nickel-cobalt-manganese compound is c, 0<c≤0.02. The types and amounts of additive III need to be strictly limited. If the types of elements are too few, the surface high entropy "cocktail" effect is not obvious. There is no clear limit on the amount of each element, but the total amount of addition is limited. Too much total amount of addition has a negative impact on the electrochemical properties of the material.

[0011] Furthermore, the high temperature calcination is a two-stage sintering process, first sintering at 450-600° C. for 1-6 hours, and then sintering at 800-1000° C. for 10-30 hours.

[0012] Furthermore, the secondary sintering temperature is 400-700° C., and the sintering time is 0.5-10 h.

[0013] Furthermore, the surface-modified high-entropy lithium-rich manganese positive electrode material provided by the present invention can be a polycrystalline material (D50 is 3-15 μm) formed by the agglomeration of primary particles, or a quasi-single crystal material (D50 is 0.1-3 μm).

[0014] The invention discloses an application of the surface modified high entropy lithium-rich manganese positive electrode material in lithium secondary batteries.

[0015] The beneficial effects of the present invention are as follows: under the premise of not affecting the capacity, a small amount of high d-state orbital elements and low electronegativity elements are co-doped, and multiple doping in the lattice generates different electrostatic fields to expand the |O2p band, enhance the overlap between the |O2p band and the (TM-O)* band, narrow the band gap, and promote the reversibility of anion redox; construct surface high entropy to change the band structure, increase the Mn 4+ The diversity and distortion energy of the local structure increase the formation energy of oxygen vacancies and the migration energy of transition metal ions, enhance the structural stability and inhibit the lattice distortion, thus increasing the Mn 4+ The local structural adaptability enhances the structural stability. Through microstructure regulation and multi-strategy coordinated regulation of the band structure, the precise design and controllable preparation of the rich layered oxide cathode material can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a scanning electron microscope image of the surface modified high entropy lithium-rich cathode material obtained in Example 1; Figure 2 is an X-ray diffraction pattern of the surface modified high entropy lithium-rich cathode material obtained in Example 1; Figure 3 This is a graph showing the cycle retention rate of the surface modified high entropy lithium-rich cathode material obtained in Example 1 under 0.5 C conditions. DETAILED DESCRIPTION

[0017] The present invention will be further described below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention, and those skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.

[0018] Example 1 The preparation method of the surface modified high entropy lithium-rich positive electrode material in this embodiment is as follows: Take Ni with D50 of 5μm0.13 Co 0.13 Mn 0.54 (OH)2 precursor, lithium salt is prepared by using lithium hydroxide monohydrate, the molar ratio of lithium hydroxide monohydrate to nickel cobalt manganese hydroxide precursor is 1.30:1, the additives are 20 nm lithium fluoride and 30 nm molybdenum oxide, the molar ratio of fluorine element to nickel cobalt manganese hydroxide is 0.002:1, the molar ratio of molybdenum element to nickel cobalt manganese hydroxide is 0.002:1, after being mixed evenly with a ball mill, first calcined at a low temperature of 550°C for 4h in a muffle furnace, and then calcined at 840°C for 20h, and then crushed, pulverized and sieved after cooling, and then mixed evenly with magnesium oxide, aluminum oxide, niobium oxide and zirconium oxide, the average particle size of magnesium oxide, aluminum oxide, niobium oxide and zirconium oxide is 50nm, and the molar ratio of magnesium element, aluminum element, niobium element, zirconium element to lithium nickel cobalt manganese oxide is 0.001: 0.001: 0.001: 0.001:1, and then sintered at 550℃ for 5h in a muffle furnace to obtain polycrystalline Li 1.20 Ni 0.13 Co 0.13 Mn 0.54 Mo 0.002 Mg 0.001 Al 0.001 Nb 0.001 Zr 0.001 O 1.998 F 0.002 .

[0019] Li 1.20 Ni 0.13 Co 0.13 Mn 0.54 Mo 0.002 Mg 0.001 Al 0.001 Nb 0.001 Zr 0.001 O 1.998 F 0.002 The scanning electron microscope image is shown in Figure 1 shown. Figure 2 For Li 1.20 Ni 0.13 Co 0.13 Mn 0.54 Mo 0.002 Mg 0.001 Al 0.001 Nb 0.001 Zr 0.001 O 1.998 F 0.002 The X-ray diffraction pattern of Figure 3 To obtain Li 1.20 Ni 0.13 Co 0.13 Mn 0.54 Mo 0.002Mg 0.001 Al 0.001 Nb 0.001 Zr 0.001 O 1.998 F 0.002 The assembled button CR2025 has a 0.5C / 0.5C cycle performance diagram. Under 0.1C conditions, the discharge capacity of the obtained material is 292 mAh / g, the capacity retention rate after 100 cycles of 0.5C / 0.5C is 95%, and the voltage decay per cycle is only 0.22mV, which has good cycle performance.

[0020] Example 2 The preparation method of the surface modified high entropy lithium-rich positive electrode material in this embodiment is as follows: Take Ni with D50 of 10μm 0.13 Co 0.13 Mn 0.54 (OH)2 precursor, lithium salt is prepared by lithium carbonate, lithium carbonate and nickel cobalt manganese hydroxide precursor in a molar ratio of 1.34:1, additives are 50 nm nano selenium oxide and 30 nm niobium oxide, the molar ratio of selenium element to nickel cobalt manganese hydroxide is 0.002:1, the molar ratio of niobium element to nickel cobalt manganese hydroxide is 0.001:1, after being mixed evenly with a ball mill, first calcined at 550°C for 3h in a muffle furnace, then calcined at 870°C for 15h, crushed, pulverized and sieved after cooling, and then mixed evenly with magnesium hydroxide, zirconium oxide, tungsten oxide and boron oxide, the average particle size of magnesium hydroxide, zirconium oxide, tungsten oxide and boron oxide is 50nm, the molar ratio of magnesium element, zirconium element, tungsten element, boron element to nickel cobalt manganese oxide is 0.002: 0.002: 0.002: 0.002:1, and then sintered at 550°C for 3h in a muffle furnace to obtain polycrystalline Li 1.18 Ni 0.13 Co 0.13 Mn 0.54 Nb 0.001 Mg 0.002 Zr 0.002 W 0.002 B 0.002 O 1.998 Se 0.002 Under 0.1 C conditions, the discharge specific capacity of the obtained material is 288 mAh / g, the capacity retention rate after 100 cycles of 0.5C / 0.5C is 93%, and the voltage decay per cycle is only 0.21 mV.

[0021] Example 3 The preparation method of the surface modified high entropy lithium-rich positive electrode material in this embodiment is as follows: 2μm Ni 0.13 Co 0.13 Mn 0.54The (OH)2 precursor was calcined at 500℃ in a muffle furnace for 3h to obtain nickel-cobalt-manganese Ni 0.13 Co 0.13 Mn 0.54 O, lithium salt is prepared by lithium carbonate, the molar ratio of lithium carbonate to nickel cobalt manganese hydroxide precursor is 1.35:1, the additives are 50 nm lithium chloride and 50 nm tungsten oxide, the molar ratio of chlorine element to nickel cobalt manganese hydroxide is 0.001:1, and the molar ratio of tungsten element to nickel cobalt manganese hydroxide is 0.001:1. After being mixed evenly with a ball mill, it is first roasted at a low temperature of 600°C for 3 hours in a muffle furnace, and then roasted at 970°C for 20 hours. After cooling, it is crushed, pulverized, and sieved, and then mixed evenly with zinc oxide, boron oxide, molybdenum oxide and niobium oxide. The average particle size of zinc oxide, boron oxide, molybdenum oxide and niobium oxide is 30nm, and the molar ratio of zinc element, boron element, molybdenum element, niobium element to nickel cobalt manganese oxide is 0.002: 0.002: 0.001: 0.001:1. Then, after sintering at 600°C for 5 hours in a muffle furnace, a single-crystal Li 1.18 Ni 0.13 Co 0.13 Mn 0.54 W 0.001 Zn 0.002 B 0.002 Mo 0.001 Nb 0.001 O 1.999 Cl 0.001 Under 0.1 C conditions, the discharge specific capacity of the obtained material is 284 mAh / g, the capacity retention rate after 100 cycles of 0.5C / 0.5C is 92%, and the voltage decay per cycle is only 0.21 mV.

[0022] Comparative Example 1 (Based on Example 1, without Additive I) In this comparative example 1, lithium fluoride was not added, and other experimental conditions were consistent with those in Example 1. The final material obtained was Li 1.20 Ni 0.13 Co 0.13 Mn 0.54 Mo 0.002 Mg 0.001 Al 0.001 Nb 0.001 Zr 0.001 Under O2, 0.1 C conditions, the discharge specific capacity of the obtained material is 293 mAh / g, the capacity retention rate after 100 cycles of 0.5C / 0.5C is 92%, and the voltage decay per cycle is 0.25 mV.

[0023] Comparative Example 2 (Based on Example 1, without Additive II) In this comparative example 2, molybdenum oxide was not added, and other experimental conditions were consistent with those in Example 1. The final material obtained was Li1.20 Ni 0.13 Co 0.13 Mn 0.54 Mg 0.001 Al 0.001 Nb 0.001 Zr 0.001 O 1.998 F 0.002 Under 0.1 C conditions, the discharge specific capacity of the obtained material is 290 mAh / g, the capacity retention rate after 100 cycles of 0.5C / 0.5C is 91%, and the voltage decay per cycle is 0.26 mV.

[0024] Comparative Example 3 (Based on Example 1, the number of additives III is reduced) In this comparative example 3, zirconium oxide was not added, and other experimental conditions were consistent with those in Example 1. The final material obtained was Li 1.20 Ni 0.13 Co 0.13 Mn 0.54 Mg 0.001 Al 0.001 Nb 0.001 O 1.998 F 0.002 Under 0.1 C conditions, the discharge specific capacity of the obtained material is 294 mAh / g, the capacity retention rate after 100 cycles of 0.5C / 0.5C is 90%, and the voltage decay per cycle is 0.27 mV.

[0025] Comparative Example 4 (Based on Example 1, the molar ratio of lithium hydroxide monohydrate to nickel cobalt manganese hydroxide precursor was adjusted to 1.25:1) In this comparative example, the molar ratio of lithium hydroxide monohydrate to nickel cobalt manganese hydroxide precursor was adjusted to 1.25:1, and other experimental conditions were consistent with those in Example 1. The final material obtained was Li 1.15 Ni 0.13 Co 0.13 Mn 0.54 Mo 0.002 Mg 0.001 Al 0.001 Nb 0.001 Zr 0.001 O 1.998 F 0.002 Under 0.1 C conditions, the discharge specific capacity of the obtained material is 288 mAh / g, the capacity retention rate after 100 cycles of 0.5C / 0.5C is 94%, and the voltage decay per cycle is 0.23 mV.

[0026] Comparative Example 5 (Based on Example 1, the molar ratio of lithium carbonate to nickel-cobalt-manganese hydroxide precursor was adjusted to 1.40:1) In this comparative example, the molar ratio of lithium hydroxide monohydrate to nickel cobalt manganese hydroxide precursor was adjusted to 1.40:1, and other experimental conditions were consistent with those in Example 1. The final material obtained was Li 1.33 Ni 0.13 Co 0.13 Mn 0.54 Mo 0.002 Mg 0.001 Al 0.001 Nb 0.001 Zr 0.001 O 1.998 F 0.002 Under 0.1 C conditions, the discharge specific capacity of the obtained material is 294 mAh / g, the capacity retention rate after 100 cycles of 0.5C / 0.5C is 90%, and the voltage decay per cycle is 0.25 mV.

[0027] Comparative Example 6 (Based on Example 1, the high temperature roasting stage adopts 780°C) In this comparative example, the high temperature calcination temperature was adjusted to 550°C for 4 hours, and then calcined at 780°C for 20 hours. The other experimental conditions were consistent with those in Example 1. The final material obtained was Li 1.22 Ni 0.13 Co 0.13 Mn 0.54 Mo 0.002 Mg 0.001 Al 0.001 Nb 0.001 Zr 0.001 O 1.998 F 0.002 Under 0.1 C conditions, the discharge specific capacity of the obtained material is 282 mAh / g, the capacity retention rate after 100 cycles of 0.5C / 0.5C is 93%, and the voltage decay per cycle is 0.23 mV.

[0028] Comparative Example 7 (Based on Example 1, the high temperature roasting stage adopts 1020°C) In this comparative example, the high temperature calcination temperature was adjusted to 550°C for 4 hours, and then calcined at 1020°C for 20 hours. The other experimental conditions were consistent with those in Example 1. The final material obtained was Li 1.18 Ni 0.13 Co 0.13 Mn 0.54 Mo 0.002 Mg 0.001 Al 0.001 Nb 0.001 Zr 0.001 O 1.998 F 0.002Under 0.1 C conditions, the discharge specific capacity of the obtained material is 280 mAh / g, the capacity retention rate after 100 cycles of 0.5C / 0.5C is 86%, and the voltage decay per cycle is 0.31 mV.

[0029] Comparative Example 8 (Based on Example 1, the secondary sintering temperature was 380°C) In this comparative example, the secondary sintering temperature was adjusted to 380°C, and other experimental conditions were consistent with those in Example 1. The final material obtained was Li 1.21 Ni 0.13 Co 0.13 Mn 0.54 Mo 0.002 Mg 0.001 Al 0.001 Nb 0.001 Zr 0.001 O 1.998 F 0.002 Under 0.1 C conditions, the discharge specific capacity of the obtained material is 288 mAh / g, the capacity retention rate after 100 cycles of 0.5C / 0.5C is 92%, and the voltage decay per cycle is 0.26 mV.

[0030] Comparative Example 9 (Based on Example 1, the secondary sintering temperature was 730°C) In this comparative example, the secondary sintering temperature was adjusted to 730°C, and other experimental conditions were consistent with those in Example 1. The final material obtained was Li 1.19 Ni 0.13 Co 0.13 Mn 0.54 Mo 0.002 Mg 0.001 Al 0.001 Nb 0.001 Zr 0.001 O 1.998 F 0.002 Under 0.1 C conditions, the discharge specific capacity of the obtained material is 280 mAh / g, the capacity retention rate after 100 cycles of 0.5C / 0.5C is 92%, and the voltage decay per cycle is 0.21 mV.

[0031] The above test results are shown in Table 1.

[0032] Table 1 Test results It can be concluded from Comparative Examples 1, 2, 3 and Example 1 that doping and high entropy surface coating can improve the cycle performance of the material and reduce voltage decay. It can be concluded from Comparative Examples 4, 5, 6, 7, 8, 9 and Example 1 that controlling the amount of lithium source added and the sintering process can improve the cycle performance of the material and reduce voltage decay. The present invention dopes heterostructures and constructs surface high entropy, and coordinates the band structure with multiple strategies to achieve precise control of the material structure, thereby improving the cycle performance and reducing voltage decay.

[0033] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A surface modified high entropy lithium-rich manganese positive electrode material, characterized in that: The lithium-rich manganese positive electrode material is represented by the general formula Li1+xNi0.13Co0.13Mn0.54MyNzO2-wAw, M is selected from one element of Cr, Mo, W, V, Nb, and Ta in a high d-state orbital, A is selected from one element of F, S, Se, and Cl with high electronegativity, N is selected from at least four elements of Mg, Nb, Cr, Ti, Mo, Al, B, Ca, Zn, Sn, W, Ce, Zr, and Sr, 0.18≤x≤0.25, 0<y≤0.01, 0<z≤0.02, and 0<w≤0.

01.

2. The method for preparing the surface modified high entropy lithium-rich manganese positive electrode material according to claim 1, characterized in that: The nickel-cobalt-manganese compound, lithium source, additive I and additive II are weighed respectively and mixed evenly, and then calcined at high temperature in a muffle furnace. After cooling, they are crushed, pulverized and sieved, and then mixed with additive III and sintered for a second time to obtain a surface high-entropy lithium-rich manganese positive electrode material.

3. The method for preparing the surface modified high entropy lithium-rich manganese positive electrode material according to claim 2, characterized in that: The nickel-cobalt-manganese compound is nickel-cobalt-manganese hydroxide, nickel-cobalt-manganese carbonate, or nickel-cobalt-manganese oxide, and has an average particle size D50 of 1-15 μm. The nickel-cobalt-manganese oxide is obtained by pre-calcining nickel-cobalt-manganese hydroxide or nickel-cobalt-manganese carbonate at a high temperature of 300-700° C. for 1-10 hours.

4. The method for preparing the surface modified high entropy lithium-rich manganese positive electrode material according to claim 2, characterized in that: The lithium source is selected from at least one of lithium carbonate, lithium hydroxide monohydrate, lithium bicarbonate, lithium oxalate, lithium nitrate or lithium acetate. The molar ratio of the lithium source to the nickel-cobalt-manganese compound is (1.30-1.35):

1. The lithium sources used are all battery grade, and the average particle size D50 is 3-15 μm.

5. The method for preparing the surface modified high entropy lithium-rich manganese positive electrode material according to claim 2, characterized in that: The additive I is a compound containing anions F, S, Se or Cl, the additive II is a compound containing high d-state orbits Cr, Mo, W, V, Nb or Ta, the average particle size D50 of the additive I and the additive II is 10-100 nm; the molar ratio of the additive I to the nickel-cobalt-manganese compound is a, 0<a≤0.01, and the molar ratio of the additive II to the nickel-cobalt-manganese compound is b, 0<b≤0.

01.

6. The method for preparing the surface modified high entropy lithium-rich manganese positive electrode material according to claim 2, characterized in that: The additive III is a mixture of at least four oxides or hydroxides of Mg, Nb, Cr, Ti, Mo, Al, B, Ca, Zn, Sn, W, Ce, Zr, and Sr, and the average particle size D50 of the additive III is 10-100 nm; the molar ratio of the additive III to the nickel-cobalt-manganese compound is c, 0<c≤0.

02.

7. The method for preparing the surface modified high entropy lithium-rich manganese positive electrode material according to claim 2, characterized in that: The high temperature calcination is a two-stage sintering process, first sintering at 450-600° C. for 1-6 hours, and then sintering at 800-1000° C. for 10-30 hours.

8. The method for preparing the surface modified high entropy lithium-rich manganese positive electrode material according to claim 2, characterized in that: The secondary sintering temperature is 400-700° C., and the sintering time is 0.5-10 h.

9. The method for preparing the surface modified high entropy lithium-rich manganese positive electrode material according to claim 2, characterized in that: The surface high entropy lithium-rich manganese cathode material is a polycrystalline material formed by primary particle agglomeration, and D50 is 3-15 μm; or, the surface high entropy lithium-rich manganese cathode material is a quasi-single crystal material, and D50 is 0.1-3 μm.

10. Use of the surface modified high entropy lithium-rich manganese positive electrode material according to claim 1 in a lithium secondary battery.

Citation Information

Patent Citations

  • Layered lithium-rich manganese-based high-entropy positive electrode material, preparation method thereof and battery

    CN115513449A

  • A medium-high entropy layered lithium-rich cathode oxide and preparation method thereof

    CN115566186B

  • A high-entropy lithium-rich layered cathode material for marine environments and its preparation method

    CN116230917B

  • Ring block friction-wear testing machine for simulating magnetic field and dynamic water environment

    CN117191621A

  • High-entropy doped layered lithium-rich manganese-based positive electrode material and preparation method thereof

    CN117712339A

Cited By

  • Modified lithium-rich manganese-based positive electrode material, preparation method thereof and solid-state battery

    CN121974408A